Media revolutions: the transformations of the digital age in light of the invention of the printing press - Schmitt, Juliana (MATRIZes, 2021)
This text presents a review of the book Gutenberg’s Europe: the book and the invention of western modernity, by the French historian Frédéric Barbier, released in France in 2006 and in Brazil in 2018 – a translated version to Portuguese published by Edusp. The author traces a historical panorama of the emergence of the movable-type printing press, focusing the social, economic and cultural processes that precede it and that succeed it, covering, therefore, more than three centuries. His aim is to draw a parallel between the revolution caused by the printing press and the current digital revolution, its causes and consequences.